PREDIKSI HASIL PENJURUSAN SISWA SEKOLAH MENENGAH ATAS DENGAN MENGGUNAKAN ALGORITMA DECISION TREE C4.5 - Imam Sujaj; Purwanto Purwanto; Heribertus Himawan (Jurnal Teknologi Informasi - Cyberku (JTIC), 2017)
The Majors is one of the placement or distribution process in the selection of high school students teaching program. In these majors, students are given the opportunity to choose majors that best matches the characteristics themselves. The accuracy in choosing majors can determine the success of student learning. In contrast, an excellent opportunity for students will be lost due to lack of inaccuracy in determining the majors. In the 2013 curriculum, majors in high school started in class X after being accepted as a student, so the school should really be able to classify students on the correct corresponding majors talents and interests of students. In studies using the C4.5 algorithm to create a predictive model results placement of students because this method has been used a lot in previous studies to predict the various cases problems with good results. This is evident from the results of the C4.5 algorithm generates a classification accuracy of 96.04% value with a precision of 95.96% class, class recall of 95.92% while the value of AUC (Area Under the Curve) of 0948 + / - 0.028 with very good category. It can be concluded that in order to predict the value of the majors C4.5 algorithm produces accuracy that is very good value.